Pengembangan Multimedia Pembelajaran IPA pada Materi Spesialisasi Sel Kelas VIII SMP - Yelsi, Nengsi Fitri; Hidayati, Abna; Yusri, Meldi Ade Kurnia; Masnur, Alkadri (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The development of this multimedia learning is motivated by the problem of learning, where teachers only use printed books as the main learning media in the classroom. Students tend to feel bored and less interested in following lessons using printed books that only contain text and images. This research aims to produce valid and practical multimedia learning products that can be used in the learning process. The type of research used is research and development, also known as Research and Development (R&D). The development model used is the 4D model, which consists of four main stages: define, design, development, and disseminate. The product validity test was conducted by 4 validators, namely 2 material validators and 2 media validators. The product trial was conducted on 20 eighth-grade students of SMP Negeri 5 Linggo Sari Baganti with the aim of determining the practicality of the developed product. The results of the material validation by 2 material validators obtained an average score of 4.93 with the category